2014
DOI: 10.3168/jds.2013-7160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supplementation of n-3 fatty acids from fish and flax oil on cytokine gene expression and growth of milk-fed Holstein calves

Abstract: The ability to reduce incidence of disease in calves and improve early vaccination strategies is of particular interest for dairy producers. The n-3 fatty acids have been reported to reduce inflammatory diseases in humans but limited research has been done in calves. The objective of this study was to compare supplementation of n-3 fatty acids from fish and flax oil on gene expression of whole blood cells and growth of milk-fed Holstein calves. Forty-eight Holstein bull calves from a commercial dairy were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 35 publications
7
50
3
Order By: Relevance
“…The linseed fatty acids have been reported to affect cytokine gene expression. For example, calves supplemented with flax oil (but not fish oil) tended to show a decrease in the expression of IL-4 and IL-8 genes (Karcher et al, 2014). The simultaneous consumption of omega-3 and omega-6 acids in a proper ratio is essential in cancer prevention and inflammation reduction.…”
Section: Seeds and Oilmentioning
confidence: 97%
“…The linseed fatty acids have been reported to affect cytokine gene expression. For example, calves supplemented with flax oil (but not fish oil) tended to show a decrease in the expression of IL-4 and IL-8 genes (Karcher et al, 2014). The simultaneous consumption of omega-3 and omega-6 acids in a proper ratio is essential in cancer prevention and inflammation reduction.…”
Section: Seeds and Oilmentioning
confidence: 97%
“…In cattle, daily dietary supplements of n-3 fatty acids (FA) have been recognized for their influence on health (Moallem, 2018), inflammation, and oxidative stress . Previous studies indicate that n-3 FA supplementation to milk replacer improved growth, health, or indicators of immune function in calves Karcher et al, 2014). This is accomplished in part by production of anti-inflammatory n-3 FA metabolites coupled with antioxidant properties .…”
Section: Introductionmentioning
confidence: 99%
“…While research has shown how different sources of omega‐3 fatty acids affect lipid profile and cytokine gene expression, there is a lack of research to determine the mechanisms whereby different sources of omega‐3 fatty acids affect blood pressure . It is suggested that further research is necessary to adequately study this topic to determine how the dietary source of omega‐3 fatty acids plays a role in lowering blood pressure and differentially affecting systolic and diastolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%